Manusia Sebagai Hamba: Mengatasi Agnostik Agama Melalui Pemahaman Tauhid menurut Naquib Al-Attas - Muchyiddin, Abdillah Khayyi; Rizqi, Alfian Fatih (PT. Student Rihlah Indonesia, 2025)
The phenomenon of religious agnosticism is becoming increasingly prevalent in the modern era, characterized by skepticism about the existence of God and a weakening of human values, identity, and meaning of life. This condition has implications for moral crisis, disorientation of life goals, and existential alienation. This study aims to analyze the concept of tawhid according to Syed Muhammad Naquib al-Attas as a philosophical and theological response to the problem of religious agnosticism, while also offering a paradigm that restores human awareness as servants of Allah. The methodology used is a qualitative approach through library research with hermeneutic analysis of Al-Attas' primary works, as well as a critical review of secondary literature related to agnosticism and Islamic theology. The results of the study show that tauhid, in Al-Attas' view, is not only a theological principle but also an epistemological and metaphysical foundation that integrates all aspects of life, guides the search for meaning, and affirms humanity's position before God. The novelty of this research lies in the synthesis between epistemological criticism of agnosticism and the offer of a comprehensive solution based on the Islamic worldview, which has implications for the formulation of educational and cultural policies that emphasize the internalization of tauhid values to shape individuals of integrity, knowledge, and civilization.